TINDAK PIDANA PENGANIAYAAN YANG DIRENCANAKAN MENGAKIBATKAN LUKA BERAT: The Planned Criminal Act of Assault Resulted in Serious Injury - Daffa Fauzan Wanutama; Vientje Ratna Multiwijaya (Reformasi Hukum Trisakti, 2024)
There have been cases of abuse that resulted in serious injuries to the victim, a stabbing that effects the chest can cause death and this act carried out with prior planning by the defendant Andes with took a pair of scissors from inside his house then chased the victim and stabbed him with the scissors. Through a case study of Decision No. 236/Pid.B/2020/PN Tbk, then the problem formulation that the author can put forward in the research, namely whether the perpetrator of the criminal act of abuse was commited planned to cause serious injury is appropriate based on Article 351 paragraph (2) Criminal Code. This research uses a normative juridical type of research analytical descriptive, using types of secondary data obtained through study literature and processed qualitatively then draw conclusions deductively. The research concludes that the perpetrator's act of planned maltreatment causing serious injury isn't suitable under Article 351 paragraph (2) of the Criminal Code. Given the premeditation involved, Article 353 paragraph (2) of the Criminal Code is more fitting. The conclusion is that the verdict's punishment imposition is inappropriate.